THE ESTABLISHMENT OF A VIRTUAL EMBASSY ACCORDING TO THE 1961 VIENNA CONVENTION ON DIPLOMATIC RELATIONS: THE CASE OF BARBADOS’ METAVERSE EMBASSY - Zhahira, Tsabita; Christianti, Diajeng Wulan (Jurnal Bina Mulia Hukum, 2023)
Through years of practice, embassies are considered the pillar of the diplomatic system, which faced developments of methods recently heavily influenced by internet optimization. It is reflected in the growing practices of non-physical embassies that raised the issue of whether or not those practices are consistent with the embassy's function under diplomatic law. By using method of normative legal research, qualitative methodology, and descriptive and comparative methods, This paper argues the difficulties of the performance of diplomatic mission function by non-physical embassies through the dimensions of efficiency laid down under the object and purpose of the Vienna Convention on Diplomatic Relations 1961. It stands to prove the cumulativeness of the functions prescribed under Article 3 (1) of VCDR, arguing that the functions' performance is inefficient by only operating one or several functions. By this way of interpretation, the sole establishment of non-physical embassies, such as virtual embassies and especially metaverse embassies, is impractical due to their inability to perform several key functions of the diplomatic mission. It then clearly established that States cannot rely solely on establishing non-physical embassies and must seek alternative methods.